Oral microbiome diversity shapes the association between sleep duration and depression - Liu, Yan; Zhang, Ling; Yang, Can; Zhi, Liping; Steven Xu, Xu; Yuan, Min (Frontiers in Neurology, 2024)
Background Emerging research suggests the relationship between the oral microbiome and sleep duration with depression, however, the precise mechanisms by which oral microbial diversity influences the sleep-depression nexus remain to be elucidated. Methods We analyzed data from 4,692 participants in the National Health and Nutrition Examination Survey (NHANES), incorporating key demographic variables, oral microbiome diversity metrics, sleep duration, and depression assessment variables. Classical multidimensional scaling facilitated dimensionality reduction, while unsupervised clustering divided participants into groups based on β-diversity dissimilarity matrices. We examined the moderating effects of oral microbiome diversity on the sleep-depression relationship by incorporating interaction terms sleep-oral microbiome diversity into multiple linear regression models. Results Our analysis revealed a U-shaped relationship between sleep duration and depression. Specifically, α-diversity was a significant moderator, with reduced diversity linked to an increased depression risk in participants with insufficient sleep. Regarding β-diversity, using both Bray-Curtis and UniFrac distance measures, Cluster 2 exhibited the strongest associations in sleep-deprived individuals (Bray-Curtis: β = 1.02, p < 0.001; Weighted UniFrac: β = 0.91, p < 0.001). In contrast, Cluster 1 displayed notable effects in individuals with excessive sleep (Bray-Curtis: β = 0.63, p = 0.008). Additionally, Cluster 3 was prominently associated with depression in sleep-deprived participants using unweighted UniFrac distance (β = 0.93, p < 0.001), and Cluster 2 was significant among those with excessive sleep across both unweighted (β = 0.80, p = 0.0004) and weighted UniFrac distances (β = 0.60, p = 0.001). Conclusion This study highlights the crucial role of oral microbiome diversity in moderating the U-shaped relationship between sleep duration and depression risk.